Efficacy of Cellulolytic Bacteria Consortium for Composting Oil Palm Empty Bunches Containing Phytonutrients - Aini, Diah Nurul; Linda, Tetty Marta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Oil palm empty fruit bunches (OPEFB) are themost solid palm oil waste. OPEFB has often been processed into compost with the addition of certain activators. It is expected that with the addition of a consortium bioactivator composting of OPEFB can be faster and the compost produced has good nutrient content. The study aims was to determine the ability of bioactivator bacteria of cellulolytic consortium in degrading TKKS of incubation laboratory scale for 30 days. A consortium of compost bioactivator used were Bacillus sp. S43, Bacillus cereus strains of IARI-MB-6, Bacillus cereus strains TS11, Alcaligenes faecalis strains ZJUTBX11, Bacillus sp. 13847, Stenotrophomonas sp. S169-III-5, Alcaligenes faecalis strains KH-48 and Bacillus cereus strain Y22 by a comparison of 1:1:1:1:1:1:1:1. The results showed that bioactivator consortium was able to degrade OPEFB which on P4 (OPEFB + chicken manure + consortium isolate) reduced organic C from 50.1 to 34.5, increased total nitrogen from 0.73 to 1.35 and reduced the C/N ratio from 37.11 to 25.56 and produced compost phytonutrients and not phytotoxicity.